Les politiques sportives en Argentine et au Brésil: D'une structuration formelle à un engagement pluriel - Levoratti, Alejo (2023)
At the beginning of the 21st century, several left and centre-left governments came to power inSouth American countries. Argentina, Brazil, Bolivia, Chile, Ecuador, Paraguay, Uruguay andVenezuela are particularly concerned and will shape sports policies with regard to this newpolitical configuration. This article intends to make a comparison between the sports publicpolicies carried out by the two largest countries in South America (Argentina and Brazil),showing what have been the similarities and differences between the Kirchnerist and Lulistpolicies in the sports sphere between the years 2003-2016. The study highlights that Argentinaand Brazil have consolidated a sports policy emphasizing social inclusion through sport andattention to sport for all. Nevertheless, the hosting of several major sporting events has changedthe initial objectives.